ChemInform Abstract: Mixed‐Valent Selenium Ligands in the Uncharged Iridium Complexes [Ir4Se10Br16] and [Ir6Se8Cl30]. Issue 47 (November 2015) - Stolze, Karoline; Rasche, Bertold; Ruck, Michael
Abstract: The crystal structures of the new compounds (IV) and (VI) are determined by single crystal XRD.